The Effect of Work Stress and Work-Family Conflict on Turnover Intention through Job Satisfaction (Case Study on Nurses at XYZ Hospital in Tasikmalaya) - Gabriela Lintang Cristandy; Yohana F. Cahya Palupi Meilani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of work-family stress, job stress on job satisfaction, work-family conflict on job satisfaction, job stress on turnover intention, work-family conflict to turnover intention, and job satisfaction to turnover intention. By using a quantitative research paradigm with a descriptive approach and hypothesis testing (hypothesis test). The sampling method was carried out using a non-probability sampling method in a purposive manner with a sample of 170 permanent nurses and at least 2 years of work at XYZ Hospital, analyzed using PLS-SEM software. The results of data analysis show that, work-family conflict has a positive effect on job stress, job stress has a negative effect on job satisfaction. Work-family conflict has a negative effect on job satisfaction. Job stress has a negative effect on turnover intention. Work-family conflict has a negative effect on turnover intention. Job satisfaction has a negative effect on turnover intention.